Tibial Condyle Valgus Osteotomy for Ipsilateral Knee Osteoarthritis after Hip Arthrodesis - Daisuke Fukuhara; Hiroaki Inoue; Shuji Nakagawa; Yuji Arai; Kenji Takahashi (Case Reports in Orthopedics)
We report a case of tibial condylar valgus osteotomy (TCVO) for ipsilateral knee osteoarthritis (OA) after hip arthrodesis. A 58-year-old woman developed right purulent hip arthritis at one month of age and underwent right hip fusion at 16 years old. She visited our department at the age of 57 because her right knee joint pain worsened. The range of motion for her right knee was 80° and -5° of flexion and extension, respectively, and she experienced medial weight-bearing pain. A plain X-ray image showed that the right knee joint had end-stage knee OA with a bone defect inside the tibia, and the tibial plateau shape was the pagoda type. There was a marked instability in her right knee with a valgus of 9° and varus of 7° on stress photography. She underwent TCVO on her right knee and was allowed full load four weeks after surgery. Computed tomography imaging showed bone union nine months after surgery. Two years after the operation, there was no correction loss, and she could walk independently without pain. In general, total knee arthroplasty (TKA) is indicated for end-stage knee OA; however, there are problems, such as early loosening due to the increased mechanical load on the knee after hip OA. In this case, since a good course was obtained, TCVO is considered a treatment option for terminal knee OA after hip arthrodesis.